Nonoxidizing heating of chip‑powder dispersions of ferrous metals in hydrocarbon atmosphere - O. M. Dyakonov; V. Yu. Sereda (Литьë и металлургия, 2021)
The process of inorganic and organic components temperature transformation of metal waste into solid and gaseous products in a continuous hot briquetting muffle furnace has been studied. The composition of the hydrocarbon atmosphere formed in the muffle under conditions of limited access to the oxidizer has been determined. It is shown that the thermal destruction of the coolant oil phase proceeds according to a complex mechanism of consecutive reactions, including polycondensation, polymerization, and deep compaction with a constant decrease in the hydrogen content and ends with the formation of a coke‑like carbon residue on the surface of metal particles and an air suspension of finely dispersed carbon particles (smoke). When it is heated to hot briquetting temperatures of 750–850 °C, chemically active dispersions of ferrous metals are protected from oxidation first by a hydrocarbon gas with a density of 9.0–13.5 kg/m3, then by a pyrocarbon coating with a thickness of 0.1–0.3 mm up to the completion of the processes of pressing and cooling the briquette.